The Impact of Pre-surgical Orthopedics Appliances (PSOAs) in Bilateral Cleft Lip and Palate (BCLP) Patients - Mohamad Shah, Nurul Syazana; Wan Makhtar, Wan Ratmaazila; Ainuddin Yeap, Saliza; Wan Sulaiman, Wan Azman; Abdullah , Ahmad Burhanuddin (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: Acceptable maxillary growth in bilateral cleft lip and palate (BCLP) is difficult to achieve. Pre-surgical orthopedic treatment aims at the reduction of cleft size by guiding growth and functional rehabilitation. The objective of this study was to evaluate the impact of Pre-surgical Orthopedics Appliances (PSOAs) on facial growth in BCLP. MATERIALS AND METHODS: Consented subjects were patients who were treated in Hospital Universiti Sains, Malaysia, and Hospital Raja Perempuan Zainab II. Ages of patients ranged from 7 to 21 years of age with non-syndromic cleft and no associated anomalies. A lateral cephalogram was taken and data collected was analyzed to compare the facial growth of BCLP with and without PSOA and between active and passive PSOA. RESULTS: The study sample comprised of 52 BCLP patients with 26 having PSOA and 26 did not having PSOA. Among these patients, those who had PSOA had significant shorter length of PNS-ANS (3.69 mm; p= 0.04) and Co-A (8.38 mm; p=0.04) compared to those who did not have PSOA. However, there were no significant difference in the length measurements between passive and active PSOA users. CONCLUSION: The usage of PSOA gives a shorter maxillary length in the facial growth of bilateral cleft patients. This study proved the effectiveness of PSOA on facial growth of cleft patients in local population.